Transfer and counter-transfer in ethnographic research - Zlatanović Sanja (Glasnik Etnografskog Instituta SANU, 2010)
A researcher and his/hers informants stand as the key players in a fieldwork discourse, thus their interaction is a key problem of fieldwork performed by ethnologists and anthropologists. This paper aims to shed light on the roles of a researcher and informants and their mutually sustainable relationship formed in a research process. This fieldwork based relationship is very sensitive, burdened by many problems related to transfer and counter-transfer set about for a researcher to analyze and keep under control at all times. The notion of transfer was introduced into psychotherapy by Freud, but it is applicable as well onto all other human interactions. During the course of a fieldwork, informants can transfer a variety of feelings, thoughts and fantasies upon a researcher, who may or may not resemble some special persons from the informants' respective lives hence influencing the informants' behavior accordingly. A positive transfer is beneficial, as it tends to 'open up' the informant, while the negative one manifests in the informant's resistance toward cooperation, hiding of important information and so on. On the other hand, the actual appearance of an informant, his/hers behavior and accounts could also trigger various emotional, often subconscious, counter-transfer reactions. In this sense, a counter-transfer is a transfer by a researcher toward his/hers informants. For example, informants could, in their accounts, by saying this or that stir a researcher's negative associations and thus provoke counter-transfers with negative connotations (avoidance of particular informant, cessation of conversation, disinterest in informants' subjects, lack of empathy etc). This is why a researcher has to keep under control his/hers potential counter-transfer expressions; uncontrolled manifestation could cause various problems and burden the research process furthermore.